The Volition of Intelligence. - Moon, Todd K. (Journal of the Utah Academy of Sciences, Arts & Letters, 2014)
Computer "intelligence," or artificial intelligence, appears to be making increasing inroads, as evidenced by computers' increasing influence on our lives and by successes in competitions between humans and computers. Despite these advances, computers continue in merely subservient roles, never exhibiting the ability to truly choose for themselves. In this paper, we explore this question of volition. We argue against Turing's test as a means of showing intelligence because it fails to test for volition. Gödel's theorem is used as an example of the result of human volition, and computer's lack of it, and we discuss the theorem in response to Hofstadter's and Penrose's views. We speculate on the possibility that computers may someday be capable of their own volition, and contemplate the risks of the possibility.